Constitutional and Conventional Reasoning of International and Regional Courts: How Do Jurisdictions that Protect Human Rights Dialogue? - Mancini, Luna (Revista Internacional & Comparada de Derechos Humanos, 2024)
Studying the reasoning of the main international and regional human rights courts and analyzing how it impacts and relates to the models of constitutional reasoning of legal systems belonging to varied legal cultures is key at a time when, in Mexico, core aspects regarding the validity of international human rights law in the domestic sphere are still being defined. Therefore, from a comparative perspective that emphasizes the unique aspects of each country, region, and court addressed, this analysis seeks to approach the courts that effectively protect human rights to understand how international criteria, both from the universal system and from regional systems, are integrated into national legal systems. To this end, some mentions are made about the internalization of constitutional law as context, followed by addressing the importance of harmonizing international criteria to protect the rights of all people and the implications of dialogue between courts, with particular attention to the coincidences and contrasts existing in the current and historical contexts of Europe and America. Finally, it is pointed out how all of the above fits into the current Mexican framework.